Plant breeding and cultivar development - Singh, Dhan Pal; Singh, Asheesh K. (Plant pathologist); Singh, Arti (Academic Press, an imprint of Elsevier, 2021)
Plant Breeding and Cultivar Development features an optimal balance between classical and modern tools and techniques related to plant breeding.Written for a global audience and based on the extensive international experience of the authors, the book features pertinent examples from major and minor world crops.